Characterization of Chitosan-Based Active Film with Addition of Young Coconut (Cocos nucifera) Leaf Extract - Darmono Erma; Supriyadi Supriyadi; Umar Santoso (agriTECH, 2022)
This research was aimed to investigate the potential of young coconut (Cocos nucifera L.) leaf extract as an antioxidant and antibacterial active compounds. In this study, the physical, mechanical, antioxidant, and antibacterial activity of chitosan-based film with addition of young coconut leaf extract were examined. The young coconut leaf extract was prepared by maceration using ethanol for 48 hours at room temperature. The antioxidant and antibacterial activities were determined by the DPPH and well diffusion methods, respectively. The total phenolic and flavonoids were analyzed using spectrophotometric method. The film was prepared using 1.0 and 1.5% chitosan solution added with young coconut leaf extract at 0, 0.1, and 0.3%. The characterization of the film included color, tensile strength, elongation, WVP, film morphology, identification of functional groups, and total phenolic and antioxidant activity release. The results showed that the antioxidant activity of young coconut leaf extract was IC50 of 58.61 ppm. The antibacterial activity test showed that the inhibitory zone for S. aureus, Salmonella sp., and E. coli were 17,66, 24.40, and 12.27 mm, respectively. Total phenolic and flavonoid contents were 129.27 mg GAE/g extracts and 3.92 mg QE/g extract, respectively. The color of the film was dark. The higher the concentration of chitosan and the young coconut leaf extract, the higher the tensile strength, whereas the value of elongation at break and water vapor permeability decreased. The release of total phenolic was higher in lipophilic food simulants than in an aqueous system. The result of the study reveals that chitosan-based film added with young coconut leaf extract had great potential as an active biodegradable film for food packaging systems.